Research progress in 3D-printed medicinal tablets - Naijun Dong; Hongqian Lv; Cheng Liu; Peng Zhang (Compuscript Ltd, 2022)
Three-dimensional printing (3DP) is a rapid-prototyping technology that uses a digital model file to construct an object through layer printing. This novel technology is widely used in aerospace, medicine, architecture and industrial applications. However, the pharmaceutical applications of 3DP technology remain in early stages, and the pharmaceutical industry is expected to experience a revolution in 3DP. Herein, recent research progress in 3D-printed medicinal tablets is reviewed, to provide a reference for future studies and applications of 3DP technology in pharmaceutics.